A utilização de materiais manipuláveis como metodologia de ensino das quatro operações com números naturais no ensino fundamental - GONÇALVES, Neyse Nayla Brandão (2023)
His research aimed to analyze how manipulable materials provide understanding in the teaching of the four operations (addition, subtraction, multiplication and division) of Elementary School and thus show the importance of using these teaching resources in the development of student learning in mathematics education. in a class of the 4th year of Elementary School at Escola Centro Educacional Maria Madalena, located in the municipality of Terra Alta/PA. The investigation consisted of verifying how manipulable materials can help in teaching the four basic operations. During the presentation of the manipulable material in the classroom, it was possible to observe the interest, enthusiasm and joy of the students when handling the didactic resource Golden Material, which was the chosen resource for the work of this research. The subjects of this research were students from the 4th year of Elementary School I, adopted a quantitative, qualitative and bibliographic approach, starting with a study based on objective and subjective questions regarding the Golden Material resource and the content of basic operations. The importance of using manipulable materials in teaching the four operations was verified, as it is concluded with this research that the subjects who answered the questionnaire satisfactorily understood the content of the four operations, as shown in the results of the graphs performed in the third from the time of the research.